Speaking at Iowa: A Personal Essay - Margaret Schwartz (Media Theory, 2022)
This essay describes the social and intellectual environment at the University of Iowa in the years immediately following the publication of Speaking Into The Air, exploring notions of literary and academic celebrity, power in the classroom, and intellectual lineage.